Vertical Housing for the Poor: Case Study of Kudu Block H Rusunawa in Semarang - Anam, Muhammad Khoirul; Harris, Liam; Jia, Chen (Indonesian Journal of Agrarian Law, 2025)
This article presents a comprehensive analysis of Rusunawa Kudu Block H in Semarang City, Indonesia, using secondary data from reliable sources. It explores the broader goals of Simple Rental Flats (Rusunawa) within Indonesia’s national housing policy, focusing on the development of inclusive and affordable urban housing for Low-Income Communities (MBR). The study highlights Semarang as a key case due to its high population density and limited land for housing. Rusunawa Kudu is profiled as a strategic housing complex that improves living conditions for economically disadvantaged groups. Special attention is given to Block H, a recently added structure within the complex, examining its physical condition, residential use, and social development potential. The research uses a literature review and secondary data analysis, drawing on academic publications, government documents, and credible online media. However, limited public data on Block H’s condition and resident demographics constrains deeper analysis. Findings show that Rusunawa Kudu plays a vital role in addressing housing needs for MBR, and the development of Block H signals the local government’s commitment to expanding access to affordable housing. Nonetheless, the lack of transparency and data availability hinders effective monitoring and evaluation. The article concludes by stressing the need for better documentation and open access to public data on social housing projects. Such improvements are crucial for formulating more effective and sustainable housing and urban development policies.